4R framework implementation: precision ag adoption by farmers and dealers. Issue 5 (7th September 2017) - Sposari, Melinda; Flis, Sally
Abstract : Understanding trends in 4R practice adoption by farmers and agricultural dealers helps CCAs know where there are opportunities to increase implementation and what information is key when interacting with producers. Recently, surveys were conducted to evaluate the adoption rate and the economics linked to precision ag practice adoption. Earn 0.5 CEUs in Nutrient Management by reading this article and taking the quiz at www.certifiedcropadviser.org/education/classroom/classes/512